Clinical features and visual outcomes of eye and orbital injuries in northern Thailand - W. Pipatrattanathaworn (2019)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND | 2019. Objective: To determine the characteristics and visual outcomes of eye and orbital injuries in northern Thailand. Materials and Methods: Medical records of 997 patients who had eye and orbital injuries and were treated at Nakornping Hospital and Chiang Mai University Hospital between October 2010 and September 2014 were retrospectively reviewed. The clinical features of eye and orbital injuries and the visual outcomes after treatment were assessed. The effect of initial visual acuity and types of injury on the visual outcomes was analyzed using ordinal logistic regression analysis. Results: Nine hundred ninety-seven patients (1,029 eyes) were included in the present study, 723 (72.5%) were male. The mean age was 43.5±18.7 years and 398 (39.9%) were employee. The median follow-up time was 0.1 (IQR 0 to 4.7) months. Most of the eye injuries occurred at the workplace (42.3%), followed by at home (32.4%). The most common causes were dirt, dust, or debris (30.6%) and blunt objects (21.9%). The common types of eye and orbital injuries were lamellar laceration (38.1%) and contusion (20.5%). The grades of severity of eye injury were grade 1 (66.6%), and grade 3 (16.7%). Visual acuity (VA) before and after treatment were unchanged (30.5%), better (46.9%), and worse (5.5%). Types of injury were not associated with change of visual outcome after treatment. Patients with initially legally blind or impaired vision were more likely to have improved visual outcomes than those with initially normal vision (odds ratio 8.9, 95% CI 6.37 to 12.53 and 7.9, 95% CI 5.03 to 12.47, respectively). Conclusion: Most of the eye injuries in northern Thailand occurred at the workplace caused by dirt, dust, or debris and the most common type of injury was lamellar laceration. Visual outcome was affected by the initial VA. Primary prevention should be encouraged to reduce the significant social and personal costs resulting from vision loss.